Physical fitness as a predictor of reaction time in soccer-playing children - Vanessa Santos; Nuno Casanova; Priscila Marconcin; Renata Willig; Josep Vidal-Conti; Denise Soares; Fábio Flôres (PLoS ONE, 2025)
This study investigated the relationship between reaction time (RT) and physical fitness (PF) in soccer-playing children, focusing on core strength, agility, flexibility and power. A sample of 89 boys (8.7 ±  2.2 years) participated in this investigation were conveniently chosen in a Portuguese soccer team. All participants were players in a non-competitive level. Data on PF components were collected and analysed to explore their associations with RT. The results revealed negative correlations between abdominal strength, agility, and RT, suggesting that stronger core stability and higher agility contribute to faster RT. However, other components, such as upper limb strength, flexibility, and horizontal jump performance, showed no significant correlation with RT. These findings highlight the importance of focusing on core strength and agility in training programs to enhance RT and overall performance in youth soccer. The study underscores the need for age-appropriate training interventions promoting physical and cognitive development.